Beta-blocker exposure and survival outcomes in patients with advanced pancreatic ductal adenocarcinoma: a retrospective cohort study (BETAPANC) - Le Bozec, Antoine; Brugel, Mathias; Djerada, Zoubir; Ayad, Marya; Perrier, Marine; Carlier, Claire; Botsen, Damien; Nazeyrollas, Pierre; Bouché, Olivier; Slimano, Florian (Frontiers in Pharmacology, 2023)
Preclinical studies have demonstrated the possible role of beta-adrenergic receptors in pancreatic ductal adenocarcinoma (PDAC) tumor invasion and migration. The current study aimed to explore the possible association between survival outcomes and beta-blocker (BB) exposure in patients with advanced PDAC. This retrospective single-center study included 182 patients with advanced PDAC. Clinical (age, sex, BMI, cardiovascular condition, presence (SBB) or absence (NSBB) of beta-1 selectivity of BB, exposure duration, and multimorbidity), oncological (stage and anticancer treatment regimen), and biological (renal and liver function) data were collected. The endpoints were overall survival (OS) and progression-free survival (PFS). Hazard ratios (HRs) and 95% confidence intervals (95% CIs) for survival outcomes associated with BB exposure were estimated using Cox regression model and propensity score (PS) methods. Forty-one patients (22.5%) were exposed to BB. A total of 104 patients progressed (57.1%) to PDAC and 139 (76.4%) patients died at the end of follow-up (median, 320 days; IQR, 438.75 days). When compared to the non-exposed group, there was no increase in survival outcomes associated with BB use (OS: HR = 1.38, 95% CI = 0.79–2.41, p = 0.26; PFS: adjusted HR = 0.95, 95% CI = 0.48–.88, p = 0.88). Similar results were obtained using the PS method. Compared to no BB usage, SBB use was associated with a significant decrease in OS (HR = 1.80, 95% CI = 1.16–2.80, p < 10-2). BB exposure was not associated with improved PDAC survival outcomes. Beta-1-selectivity was not independently associated with any differences.